Design and deployment of ODISEA, an application for the myOcarDial infarction SafEtytrAnsfer of patients. (April 2023) - Rodríguez, Antonio; Aboal, Jaime; Loma-Osorio, Pablo; Ramos, Rafel; Boada, Imma
Highlights: ODISEA, acronym of myOcarDial Infarction SafEtytrAnsfer, improves the transfer and management of STEMI patients. ODISEA provides an improvement in the times of first angioplasty as well as a reduction in the erroneous infarction codes activation. Professionals, specially from the hospitals with no catheterization laboratory, feel more confident with ODISEA. Abstract: Background: Rapid primary angioplasty is the most effective reperfusion strategy for acute ST-elevation myocardial infarction (STEMI) patients. Since not all hospitals have a catheterization laboratory to perform this intervention, adequate coordination of all medical professionals involved in the management of STEMI patients from the emergency room to the hospital catheterization laboratory is necessary. Objective: Present the design and deployment of ODISEA (acronym of myOcarDial Infarction SafEtytrAnsfer), a web-based environment plus an application created to complement and support the transfer and management of STEMI patients from the first medical contact to the catheterization laboratory where the primary angioplasty will be carried out. Method: ODISEA is an application that has been designed to improve the coordination of all health personnel involved in the management of STEMI patients, i.e., primary care hospitals, Emergency Medical Services [EMS] and cardiology departments. The application provides: (i) functionalities to register relevant information of the patients' and the administered medications, (ii) a chat to coordinate all involved personnel; (iii) treatment recommendations for the first medical contact; and (iv) a GPS-SATELLITE monitoring system to know the exact position of the ambulance during patient transfer. These features improve the coordination in the catheterization laboratory, and optimize the equipment preparation time, and also the patient accommodation procedures after primary angioplasty. ODISEA registers all treated cases for a proper follow-up. The application has been tested from September 2021 to January 2022 in the context of a pilot study in Girona that involved 98 patients and 42 professionals (11 from hospital without Cath lab availability, 21 from EMS, and 10 from the main hospital). Professionals answered a questionnaire using a five-point Likert scale (satisfaction level from 1 to 5) to assess ODISEA regarding patient management, care quality, transfer coordination, transfer effectiveness, and usefulness. Collected data was analyzed using chi-square or Fisher's exact test. Statistical significance has been considered p < 0.05. To evaluate times of first angioplasty, relevant data from 98 patients was collected and compared with data of 129 STEMI patients not treated with ODISEA. Results: For all the questions>70 % of answers are in the 3 to 5 range and from these, almost all the questions have 50 % of answers in the 4 and 5 range. Regarding groups of professionals only in the question related to coordination significant difference has been found for EMS professionals with respect to hospital without Cath lab availability and catheterization hospital professionals. Comparing ODISEA with no ODISEA patients it was observed an improvement in the times of first angioplasty as well as a reduction in the erroneous infarction codes activation. Patients treated with the ODISEA APP were further away from the PCI-capable center. A non-significant tendency was seen towards shorter primary angioplasty times (diagnostic electrocardiogram-guidewire passage) in the ODISEA compared to the NON ODISEA group (112 min vs 122 min; P =.3), a non-significant reduction of cases with times > 120 min (26.2 % vs 35.7 %, respectively; P =.1), and a tendency towards fewer cases eventually diagnosed as non-acute coronary syndrome (7.1 % vs 13.2 %; P =.1). Conclusion: ODISEA is a very well-accepted application that improves the management of STEMI patients. The application is an appropriate complement to current infarction protocol.